Development and preclinical evaluation of acellular collagen scaffolding and autologous artificial connective tissue in the regeneration of oral mucosa wounds - Espinosa, Lady G. (2010)
This work assessed wound healing response in rabbit oral lesions grafted with autologous artificial connective tissue or acellular collagen scaffolds. Autologous artificial oral connective tissue (AACT) was produced using rabbit fibroblasts and collagen I scaffolds. Before implantation, AACT grafts were assayed to demonstrate the presence of fibroblasts and extracellular matrix components, as well as the expression of characteristic genes and secretion of chemokines, cytokines, and growth factors. AACT grafts were tested in the rabbits from which the fibroblasts were obtained, whereas acellular collagen type I scaffolds (CS) were evaluated in a separate group of rabbits. In both cases, contralateral wounds closed by secondary intention were used as controls. In a separate experiment, AACT-grafted wounds were directly compared with contralateral CS-grafted wounds in the same animals. Wound contraction and histological parameters were examined to evaluate closure differences between the treatments in the three animal experiments performed. Contraction of wounds grafted with AACT and CS was significantly lower than in their controls (p < 0.05). Additionally, AACT significantly lowered wound contraction when compared with CS (p < 0.05). Intriguingly, it was observed that AACT-grafted wounds initially displayed a significantly higher (p < 0.05)—albeit transient—inflammatory response than seen in CS-grafted wounds and secondary healed wounds. This suggests that an early inflammatory component may contribute to tissue regeneration. Altogether, the results suggest that AACT- and CS-grafted wounds favor regeneration of oral mucosa.